Egg enrichment with n-3 fatty acids in farmed hens in sub-optimum temperature: A cold-temperament additive mix alleviates adverse effects of stress on performance and health - Hosseini, Hossein; Esmaeili, Moha; Zare, Mahyar; Rombenso, Artur (Journal of animal physiology and animal nutrition, 2022)
At some stage, laying hen farming is likely to be subjected to sub-optimum temperatures (SOTem) due to climate change. While egg enrichment with n-3 fatty acids is a common practice in the poultry industry, in SOTem it has been less investigated. This study tested the effects of egg enrichment through extruded flaxseed (FLX) (180 g/kg) alone or along with hulled-soaked barley (H-SB) (170 g/kg), namely FLBA, with and without a cold-temperament additive mix (CTA) (25 g/kg: 5 g/kg flixweed (Descurainia sophia), 10 g/kg dried herb-extraction residues from pussy willow (Salix aegyptiaca) and 10 g/kg dried lemon (Citrus limon) residue) in two temperatures (20°C and SOTem: 27°C) on egg performance, yolk fatty acids, lipid components, blood biochemistry, serological enzymes, antioxidant and immune system of Hy-Line W-36 53-week-old for 9 weeks. Two hundred seventy layers were randomly distributed to nine treatments, resulting in six replicates with five hens. Hens fed flaxseed diets, regardless of temperature or CTA, had higher levels of n-3 fatty acids in yolks than others. Temperature negatively influenced feed intake and egg production. FLX + H27 and FLBA + H27 groups outperformed the other groups regarding cholesterol in yolk (10.1, 10.3 mg/g yolk), high-density lipoprotein (HDL) (5.19, 4.93 mg/g yolk), total protein (FLX + H27: 6.82 mg/dl), HDL in the blood (FLBA + H27:83.8 mg/dl), superoxide dismutase (FLBA + H27:90.4 U/ml), glutathione reductase (FLBA + H27: 1042.1 U/ml), glutathione peroxidase (FLX + H27: 1149.7 U/ml) and catalase (FLBA + H27: 12.5 U/ml). Total antibody, immunoglobulin G and immunoglobulin M after 42 days were significantly higher in chicks fed CTA-added diets (p < 0.05). Replacing corn and soya bean meal with H-SB did not negatively change the above-mentioned factors. Our findings collectively suggest that egg enrichment with n-3 fatty acids through dietary FLBA + H27 (180 g/kg flaxseed, 170 g/kg H-SB, and 25 g/kg CTA) in SOtem is suggested without any adverse impacts.
Keywords: vaječný žloutek; Chickens; Animal Feed; Temperature; Diet; Egg Yolk; teplota; Female; Flax; egg performance; temperament; Temperament; zvířata; omega-3 mastné kyseliny; Fatty Acids, Omega-3; antioxidant system; blood cholesterol; kur domácí; mastné kyseliny; climate change; ženské pohlaví; krmivo pro zvířata; dieta; potravní doplňky; Dietary Supplements; extruded flaxseed; Animals; n-6/n-3 ratio; len; Fatty Acids